Countering terrorism, protecting critical national infrastructure and infrastructure assets through the use of novel behavioral biometrics. (1st September 2016) - Chaurasia, Priyanka; Yogarajah, Pratheepan; Condell, Joan; Prasad, Girijesh; McIlhatton, David; Monaghan, Rachel
ABSTRACT: Since 9/11, there has been an increased interest in the use of biometric technologies as a way to counter the threat of terrorism and to protect a nation's critical national infrastructure and infrastructure assets. Biometric features can be used to verify an individual's identity or in the identification of an individual. Such features can be divided into two types, namely physical and behavioral characteristics. Physical biometrics are concerned with direct measurements of an individual's body and would include fingerprints, facial geometry and iris patterns. In contrast, behavioral biometrics are concerned with the indirect measurements of an individual, namely their patterns of behavior such as gait, voice and keystroke dynamics. Thus, each individual has a set of unique behavioral biometric features, which they usually adhere to under normal conditions. Based on this concept it is then possible to create different behavioral biometric profiles for each individual that can distinguish one individual from another. In this paper, we propose a video-based security system using style of hand waving as a novel behavioral biometric feature for individual identification.